Code switching in student-student interaction; functions and reasons! - Amorim, Rita (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Today’s students of English will communicate mostly with non-native speakers, in predominantly non-native speaking environments. English teachers know that if they are to realistically prepare students for international communication, they must focus on speaking activities that promote communicative competence and fluency. Presence of mother tongue in communicative exchanges is frequently detected by teachers in EFL classrooms. This study analyses student-student interaction during a group-work speaking activity, to uncover some of the reasons for code switching (CS). It also presents participants’ perspectives revealing mixed feelings towards this linguistic behaviour, which is sometimes intentional and sometimes unconscious. The aim of this paper is to illustrate how EFL students alternate between foreign language and native language to perform certain pragmatic functions and counter-balance for language deficiencies. It also considers the relationship between students’ language level and the functional character of their switches.